Design and Development of a Data Warehouse for PT. CMS Using the Nine-Step Kimball Method - Ardan Habib Amirullah; Yunus Anis (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
A fully automated and structured management system in today's era is very important to support more efficient use when making decisions in a company. PT Cipta Mulia Surabaya, a company involved in the construction, mechanical, and purchasing sectors, is also one of the companies that has a management system to manage company data. Since the establishment of this company, the management system used has not used technology that has been developed in the current era or the management system is still done semi-manually, so that it can cause less than optimal in making a decision or planning. To overcome this problem, researchers created an application entitled Data Warehouse Design and utilized the Nine Step Kimball method which consists of 9 (nine) stages. With this Data Warehouse Design and Construction, it is hoped that it can help management in decision making or simplify the planning process. In the process of creating this Data Warehouse Design and Construction system, the author uses a software that functions as a local server so that it can run an application that is being developed, the author himself uses XAMPP software as a local server, in addition to being a local server, XAMPP can also manage databases. While the software for the text editor, the author uses Visual Studio Code. It is expected that with this application system, the company's performance can be optimized